Interview with Stefano Zamagni: The Italian Third Sector - Bassi Andrea (Nonprofit Policy Forum, 2011)
In Italy, the third sector includes six main sets of civil society organizations: Voluntary organizations, social cooperatives, NGO, associations of social advancement, foundations, and social enterprises. Typical of the Italian third sector is recognition of the dual nature of its organizatons: those performing a redistributive function and those performing a productive function.